Implementation of Joint Regulation Policies of the Minister of Religion and Minister of Home Affairs Number 9 and 8 of 2006 through Empowerment of Religious Harmony Forums in Manado City - Muhamad Taher Tanggung; Sri Suwitri; Endang Larasati; Rukmina Gonibala (GoAcademica Research & Publishing, 2020)
This study aims to determine how the Manado City Religious Harmony Forum from now on known as FKUB empowers the roles stipulated in Joint Regulations Number 9 and Number 8 of 2006 by the Minister of Religion and the Minister of Home Affairs. A qualitative approach was applied to this study using the literature review method. At the same time, perform data analysis in qualitative descriptions. This is because the policy's success depends very much on the role of the government, namely the government gives the authority to FKUB managers to act as a management team to deliver information on policies formulated by the central government to cities/regions. This structured accountability system is based on the bureaucracy's compliance with the upper-level bureaucracy or the designated level of bureaucracy. Is there a smooth routine procedure and whether there are problems and the expected implementation and implementation of all existing plans and plan targets—impact (benefit). Therefore, the policy implementation process's measurement is carried out to transfer information or news from a higher organization to a lower one.